The Juridical Implications of Buying and Selling Land That Is Not In Accordance with the Procedure for Making Deeds by PPAT - Baskoro, Fendy Widyo (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to find out about the procedure for making a land sale and purchase deed by PPAT, to find out what are the forms of making a land sale and purchase deed that are not in accordance with the procedure for making a deed by PPAT, to find out what factors cause the making of a deed Buying and selling land that is not in accordance with the procedure for making a deed by PPAT, to find out the legal consequences of buying and selling land that is not in accordance with the procedure for making a deed by PPAT. The normative juridical approach method is used and the data sources used are primary data and secondary data. The data collection was carried out by conducting library research and field research, then after the data was analyzed, conclusions were drawn using inductive thinking methods.Keywords: Consequences; Procedures; Selling.